Buyer Decision Process on the Market of Electric Shavers - Frič, Peter; Stříteský, Václav; Koudelka, Jan; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2010)
Buyer decision process is an important mechanism in the heads of consumers which leads them through purchase decisions. To understand behaviour of consumers, this process has to be analyzed and explained. Aim of this thesis is to analyze market of electric shavers in the Czech Republic and to determine key factors influencing purchase behaviour. Secondary and primary research are undertaken to reach the goal of the paper. In addition, five hypotheses are evaluated to verify author's expectations about the market of electric shavers for men in the Czech Republic. Analysis shows that consumers base their decisions about shavers mostly on performance and price. Though, majority of consumers do not buy shavers themselves, but receive it as a present from close family or relatives.
Vedoucí práce: Václav Stříteský
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2010
Rok obhajoby 2010
Keywords: international Management [obor dipl. práce]; spotřebitelské chování; diplomové práce; consumer behavior; master's theses